Influence of Education, Training (Diklat), Discipline and Leadership on Public Service Performance: Case Study at the Personnel and Human Resources Development Agency of South Buton Regency - Sumarni, Sumarni; Nirwana, Nirwana; Munizu, Musran (International Journal of Multidisciplinary Approach Research and Science, 2023)
This study aims to 1) identify and analyze the effect of education, training (education and training), discipline on ASN performance, 2) identify and analyze the effect of discipline on ASN performance and 3) identify and analyze the influence of leadership on ASN performance. This research approach uses quantitative research. The research was conducted at the Regional Personnel, Education and Training Agency (BKPSDM) of the Buton Selatan Regency. When the research was conducted from November-December 2023. The study population was all employees of the Regional Personnel, Education and Training Agency (BKPSDM) of the Selayar Islands Regency, totaling 68 people. The sample selection in this study was saturated sample, namely the entire population was judged as a sample so that the sample in this study was 68 people. The analysis techniques used in this research are validity, reliability, normality test, heteroscedasticity test, multicollinearity test, t hypothesis test, f hypothesis test and coefficient of determination. The data in this study were processed using SPSS 26. The results of this study indicate that: 1) There is an influence between education and training (education and training) on ASN performance, 2) there is an influence of discipline on ASN performance and 3) there is an influence of leadership on ASN performance. Education and training are the most dominant variables affecting ASN performance. The importance of education and training, discipline and leadership because it can affect the performance level of an employee